ADAM33 gene silencing by promoter hypermethylation as a molecular marker in breast invasive lobular carcinoma - Seniski, Gerusa G; Camargo, Anamaria A; Ierardi, Daniela F; Ramos, Edneia AS; Grochoski, Mariana; Ribeiro, Enilze SF; Cavalli, Iglenir J; Pedrosa, Fabio O; de Souza, Emanuel M; Zanata, Silvio M; Costa, Fabrício F; Klassen, Giseli (BMC cancer, 2009)
Background ADAM33 protein is a member of the family of transmembrane glycoproteins composed of multidomains. ADAM family members have different activities, such as proteolysis and adhesion, making them good candidates to mediate the extracellular matrix remodelling and changes in cellular adhesion that characterise certain pathologies and cancer development. It was reported that one family member, ADAM23 , is down-regulated by promoter hypermethylation. This seems to correlate with tumour progression and metastasis in breast cancer. In this study, we explored the involvement of ADAM33, another ADAM family member, in breast cancer. Methods First, we analysed ADAM33 expression in breast tumour cell lines by RT-PCR and western blotting. We also used 5-aza-2'-deoxycytidine (5azadCR) treatment and DNA bisulphite sequencing to study the promoter methylation of ADAM33 in breast tumour cell lines. We evaluated ADAM33 methylation in primary tumour samples by methylation specific PCR (MSP). Finally, ADAM33 promoter hypermethylation was correlated with clinicopathological data using the chi-square test and Fisher's exact test. Results The expression analysis of ADAM33 in breast tumour cell lines by RT-PCR revealed gene silencing in 65% of tumour cell lines. The corresponding lack of ADAM33 protein was confirmed by western blotting. We also used 5-aza-2'-deoxycytidine (5-aza-dCR) demethylation and bisulphite sequencing methodologies to confirm that gene silencing is due to ADAM33 promoter hypermethylation. Using MSP, we detected ADAM33 promoter hypermethylation in 40% of primary breast tumour samples. The correlation between methylation pattern and patient's clinicopathological data was not significantly associated with histological grade; tumour stage (TNM); tumour size; ER, PR or ERBB2 status; lymph node status; metastasis or recurrence. Methylation frequency in invasive lobular carcinoma (ILC) was 76.2% compared with 25.5% in invasive ductal carcinoma (IDC), and this difference was statistically significant (p = 0.0002). Conclusion ADAM33 gene silencing may be related to the discohesive histological appearance of ILCs. We suggest that ADAM33 promoter methylation may be a useful molecular marker for differentiating ILC and IDC.